Coordination-resolved local bond relaxation, electron binding-energy shift, and Debye temperature of Ir solid skins - Wang, Yan (2015)
Numerical reproduction of the measured 4f7/2 energy shift of Ir(100), (111), and (210) solid skins turns out the following: (i) the 4f7/2 level of an isolated Ir atom shifts from 56.367eV to 60.332 eV by 3.965 eV upon bulk formation; (ii) the local energy density increases by up to 130% and the atomic cohesive energy decreases by 70% in the skin region compared with the bulk values. Numerical match to observation of the temperature dependent energy shift derives the Debye temperature that varies from 285.2 K (Surface) to 315.2 K (Bulk). We clarified that the shorter and stronger bonds between under-coordinated atoms cause local densification and quantum entrapment of electron binding energy, which perturbs the Hamiltonian and the core shifts in the skin region.